2016
DOI: 10.1186/s12909-016-0796-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of an intervention to improve resident-fellow teaching interactions on the wards

Abstract: BackgroundSubspecialty fellows can serve as a tremendous educational resource to residents; however, there are multiple barriers to an effective resident-fellow teaching interaction in the setting of inpatient consultation. We designed and evaluated a resident-directed intervention to enhance communication and teaching during consultation on the general medicine wards.MethodsFive medical teams were randomized to receive the intervention over a 3 month period (3 control, 2 intervention teams). The intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…One initial study demonstrated the effectiveness of a "Fellow As Clinical Teacher" curriculum in improving participant skills in structured teaching exercises as well as fellow interest in teaching (E. M. Miloslavsky, Criscione-Schreiber, et al, 2016). This group also recently showed that outreach to residents on primary teams, aimed at improving the quality of consult questions and encouraging residents to ask fellows for in-person teaching, successfully increased in-person teaching interactions during consultation (Gupta, Alladina, Heaton, & Miloslavsky, 2016). These educational innovations and emphasis may help address our study's findings that one-on-one interactive education is desired but underutilized.…”
Section: Discussionmentioning
confidence: 99%
“…One initial study demonstrated the effectiveness of a "Fellow As Clinical Teacher" curriculum in improving participant skills in structured teaching exercises as well as fellow interest in teaching (E. M. Miloslavsky, Criscione-Schreiber, et al, 2016). This group also recently showed that outreach to residents on primary teams, aimed at improving the quality of consult questions and encouraging residents to ask fellows for in-person teaching, successfully increased in-person teaching interactions during consultation (Gupta, Alladina, Heaton, & Miloslavsky, 2016). These educational innovations and emphasis may help address our study's findings that one-on-one interactive education is desired but underutilized.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that teaching during consultation has many potential benefits and is desired by both residents and fellows, our previous work suggests that fellows are an underused teaching resource. 14,15 This may be because the primary team-consultant interaction is an example of situated learning 16 taking place in the academic medical center environment, which presents many potential barriers to effective consultation and an optimal learning environment. These factors can be broadly divided into interpersonal and systems issues (Box 1).…”
Section: Barriers To Effective Teaching During Consultationmentioning
confidence: 99%
“…4 We therefore, encourage resident-driven strategies to increase the teaching that residents receive, such as setting up an in-person time for follow-up communication and empowering the residents to ask for teaching during the interaction. 16 One internal medicine intervention focused on resident-driven strategies to actively engage in the teaching interaction, resulted in increased perceptions of in-person communication and number of in-person teaching interactions. 16 Residents also are discouraged from making the assumption that fellows are too busy to teach, as this perception may be inaccurate.…”
Section: Resident Interventionsmentioning
confidence: 99%
“…16 One internal medicine intervention focused on resident-driven strategies to actively engage in the teaching interaction, resulted in increased perceptions of in-person communication and number of in-person teaching interactions. 16 Residents also are discouraged from making the assumption that fellows are too busy to teach, as this perception may be inaccurate. 4…”
Section: Resident Interventionsmentioning
confidence: 99%